2023
DOI: 10.1093/cid/ciad294
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Autoimmunity Is Associated With Increased Severity of Coronavirus Disease 2019: A Retrospective Cohort Study Using Data From the National COVID Cohort Collaborative (N3C)

Abstract: Background Identifying individuals with a higher risk of developing severe COVID-19 outcomes will inform targeted or more intensive clinical monitoring and management. To date, there is mixed evidence regarding the impact of pre-existing autoimmune disease (AID) diagnosis and/or immunosuppressant (IS) exposure on developing severe COVID-19 outcomes. Methods A retrospective cohort of adults diagnosed with COVID-19 was created … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…• Rural area 13 18 (28.9) 26 19 Recent data suggest that pre-existing auto-immune disease is associated with increased severity of COVID-19, but IBD was not the most frequent auto-immune disease in the dataset and the same study showed a protective effect of anti-TNF therapy, which is the most frequently used in patients with IBD (38). Conversely, the BELCOMID study described a benign course of COVID-19 infection in a cohort of more than 2000 patients with immune mediated inflammatory diseases (IMID) of whom more than 60% had IBD (39).…”
Section: Discussionmentioning
confidence: 98%
“…• Rural area 13 18 (28.9) 26 19 Recent data suggest that pre-existing auto-immune disease is associated with increased severity of COVID-19, but IBD was not the most frequent auto-immune disease in the dataset and the same study showed a protective effect of anti-TNF therapy, which is the most frequently used in patients with IBD (38). Conversely, the BELCOMID study described a benign course of COVID-19 infection in a cohort of more than 2000 patients with immune mediated inflammatory diseases (IMID) of whom more than 60% had IBD (39).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found increased autoantibodies to be associated with COVID-19 and PASC ( 6 , 54 60 ), though the findings associating PASC and autoantibodies have been inconsistent ( 61 ). Additionally, prior autoimmunity and antibody cross-reactivity between tissue proteins and SARS-CoV-2 antigens could also be contributing to the pathophysiology of COVID-19, and hence, PASC ( 62 , 63 ). We did not observe any significant differences in antibodies against SARS-CoV-2 or other common viral pathogens between hospitalized PASC and non-PASC participants, indicating that hospitalized PASC participants likely have a functional acute immune response against the SARS-CoV-2 virus, similar to that of hospitalized non-PASC participants.…”
Section: Discussionmentioning
confidence: 99%